1996
DOI: 10.1006/jcss.1996.0003
|View full text |Cite
|
Sign up to set email alerts
|

Parameterized Pattern Matching: Algorithms and Applications

Abstract: The problem of finding sections of code that either are identical or are related by the systematic renaming of variables or constants can be modeled in terms of parameterized strings ( p-strings) and parameterized matches ( p-matches). P-strings are strings over two alphabets, one of which represents parameters. Two p-strings are a parameterized match ( p-match) if one p-string is obtained by renaming the parameters of the other by a one-to-one function. In this paper, we investigate parameterized pattern matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
263
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(265 citation statements)
references
References 19 publications
2
263
0
Order By: Relevance
“…The parameterized matching problem was introduced by Baker [10,11]. Her main motivation lay in software maintenance, where program fragments are to be considered "identical" even if variable names are different.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameterized matching problem was introduced by Baker [10,11]. Her main motivation lay in software maintenance, where program fragments are to be considered "identical" even if variable names are different.…”
Section: Introductionmentioning
confidence: 99%
“…An optimal algorithm for exact parameterized matching appeared in [5]. Approximate parameterized matching was investigated in [10,15,8]. Idury and Schäffer [16] considered multiple matching of parameterized patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Baker and Manber [7] proposed a method to deduce similarities in Java bytecodes by applying text similarity measures, such as Siff [8], parameterized pattern matching [9], and diff. Tamada et al [2], [3] first suggested a practical application of static software birthmarks and presented a method to compare the birthmarks for Java class files.…”
Section: Related Workmentioning
confidence: 99%
“…The question of how to organize and represent a text corpus for optimized retrieval and search has been motivated by diverse problems in areas of information retrieval Amir et al [1994], Blumer et al [1987] and Ferragina and Grossi [1995], pattern matching Weiner [1973], software analysis Baker [1993], and bioinformatics Bieganski et al [1994] Gusfield [1997 where there are several well developed techniques based on suffix trees McCreight [1976] Ukkonen [1985], compressed suffix trees Navarro and Mäkinen [2007], and suffix arrays Manber and Myers [1990] and Manzini and Ferragina [2004]. In addition indexing for dynamic data sets Amir et al [1994]; Ferragina and Grossi [1995] has been reported.…”
Section: Introductionmentioning
confidence: 99%